DEVELOPING ECONOMIC BEHAVIOUR BASED ON UNIVERSAL VALUES IN MAQASHID SYARIAH FOR PEACEFUL WORLD - AM. M. Hafidz MS. (Jurnal Hikmatuna, 2015)
In order to create peaceful world from economic aspect, maqashid syariah should ideally also has implications for—at least moslem—all mankind in their economic behavior, both in consumers and producers position. maqashid syariah is the reason for the existence of rules in Islamic teachings. Attaining maslahah and avoiding disobedience/disadvantageous for all mankind as universal value, should be placed as the point, so all aspect of human life should lead in achieving the desired benefit in maqashid syariah. Hence, Islamic economy also put maqashid syariah as refference, so it will be the first choice for people (not jus for moslem) to solve contemporary economic problems. Moslem scholars are in charge to apply maqashid syariah on their analysis related to economics and economy.